Fast and accurate identification by MALDI‐TOF of the zoonotic serovar E of Vibrio vulnificus linked to eel culture - Mirjam Boonstra; Belén Fouz; Betty van Gelderen; Inger Dalsgaard; Lone Madsen; Eva Jansson; Carmen Amaro; Olga Haenen (Journal of Fish Diseases, 2023)
Vibrio vulnificus is a zoonotic pathogen that can cause death by septicaemia in farmed fish (mainly eels) and humans. The zoonotic strains that have been isolated from diseased eels and humans after eel handling belong to clade E (or serovar E (SerE)), a clonal complex within the pathovar (pv.) piscis . The aim of this study was to evaluate the accuracy of MALDI‐TOF mass spectrometry (MS) in the identification of SerE, using the other two main pv. piscis ‐serovars (SerA and SerI) from eels as controls. MALDI‐TOF data were compared with known serologic and genetic data of five pv. piscis isolates or strains, and with the non pv. piscis reference strain. Based on multiple spectra analysis, we found serovar‐specific peaks that were of ~3098 Da and ~ 4045 Da for SerE, of ~3085 Da and ~ 4037 Da for SerA, and of ~3085 Da and ~ 4044 Da for SerI. Therefore, our results demonstrate that MALDI‐TOF can be used to identify SerE and could also help in the identification of the other serovars of the species. This means that zoonosis due to V. vulnificus could be prevented by using MALDI‐TOF, as action can be taken immediately after the isolation of a possible zoonotic V. vulnificus strain.

Reversible mutations in gliding motility and virulence genes: A flexible and efficient phage defence mechanism in Flavobacterium psychrophilum - Jóhanna Jørgensen; Krister Sundell; Daniel Castillo; Liv S. Dramshøj; Natasja B. Jørgensen; Susie B. Madsen; Lotta Landor; Tom Wiklund; Valentina L. Donati; Lone Madsen; Inger Dalsgaard; Mathias Middelboe (Environmental Microbiology, 2022)
Flavobacteria are among the most important pathogens in freshwater salmonid aquaculture worldwide. Due to concerns regarding development of antibiotic resistance, phage therapy has been proposed as a solution to decrease pathogen load. However, application of phages is challenged by the development of phage resistance, and knowledge of the mechanisms and implications of phage resistance is therefore required. To study this, 27 phage‐resistant isolates of F. psychrophilum were genome sequenced and characterized to identify genetic modifications and evaluate changes in phenotypic traits, including virulence against rainbow trout. Phage‐resistant isolates showed reduction or loss of gliding motility, proteolytic activity, and adhesion to surfaces, and most isolates were completely non‐virulent against rainbow trout fry. Genomic analysis revealed that most phage‐resistant isolates had mutations in genes associated with gliding motility and virulence. Reversal of these mutations in a sub‐set of isolates led to regained motility, proteolytic activity, virulence and phage susceptibility. Although costly, the fast generation of phage resistance driven by single, reversible mutations likely represents a flexible and efficient phage defence mechanism in F. psychrophilum . The results further suggest that phage administration in aquaculture systems to prevent F. psychrophilum outbreaks selects for non‐virulent phage‐resistant phenotypes.

Immersion vaccines against Yersinia ruckeri infection in rainbow trout: Comparative effects of strain differences - He Yang; Ding Zhujin; Moonika H. Marana; Inger Dalsgaard; Jaafar Rzgar; Mathiessen Heidi; Karami M. Asma; Kania W. Per; Buchmann Kurt (Journal of Fish Diseases, 2021)
The protective effects of autogenous and commercial ERM immersion vaccines (bacterins based on Yersinia ruckeri, serotype O1, biotypes 1 and 2) for rainbow trout ( Oncorhynchus mykiss ) were compared in order to evaluate whether the use of local pathogen strains for immunization can improve protection. In addition, the effect of the bacterin concentration was established for the commercial product. Following sublethal challenge of vaccinated and non‐vaccinated control fish with live bacteria, we followed the bacterial count in the fish (gills, liver and spleen). The expression of genes encoding immune factors (IL‐1β, IL‐6, IL‐8, IL‐10, IFN‐γ, MHCI, MHCII, CD4, CD8, TCRβ, IgM, IgT, IgD, cathelicidins 1 and 2, SAA and C3) and densities of immune cells in organs were recorded. Both vaccines conferred protection as judged from the reduced bacterial load in exposed fish. Innate immune genes were upregulated in all groups following bacterial challenge but significantly more in non‐vaccinated naive fish in which densities of SAA‐positive immune cells increased. Immunoglobulin genes were upregulated on day 5 post‐challenge, and fish vaccinated with the high commercial bacterin dosage showed increased IgM levels by ELISA on day 14 post‐challenge, reflecting that the vaccine dosage was correlated to protection. In conclusion, both vaccine types offered protection to rainbow trout when exposed to live Y. ruckeri and no significant difference between commercial and autogenous vaccines was established.

Genome‐informed approach to identify genetic determinants of Flavobacterium psychrophilum phage susceptibility - Castillo Daniel; Jørgensen Johanna; Sundell Krister; Madsen Lone; Dalsgaard Inger; Wiklund Tom; Middelboe Mathias (Environmental Microbiology, 2021)
Summary The fish pathogen Flavobacterium psychrophilum infects farmed salmonids worldwide, and application of bacteriophages has been suggested for controlling disease outbreaks in aquaculture. Successful application of phages requires detailed knowledge about the variability in phage susceptibility of the host communities. In this study, we analysed the genetic diversity of F. psychrophilum hosts and phages from the Baltic Sea area to identify genetic determinants of phage‐host interaction patterns. A host range analysis of 103 phages tested against 177 F. psychrophilum strains (18 231 phage–host interactions) identified nine phage clusters, infecting from 10% to 91% of the strain collection. The core genome‐based comparison of 35 F. psychrophilum isolates revealed an extremely low overall genomic diversity (>99.5% similarity). However, a small subset of 16 ORFs, including genes involved in the type IX secretion system (T9SS), gliding motility and hypothetical cell‐surface related proteins, exhibited a highly elevated genetic diversity. These specific genetic variations were linked to variability in phage infection patterns obtained from experimental studies, indicating that these genes are key determinants of phage susceptibility. These findings provide novel insights on the molecular mechanisms determining phage susceptibility in F. psychrophilum and emphasizes the importance of phages as drivers of core genomic diversity in this pathogen.

Experimental anal infection of rainbow trout with Flavobacterium psychrophilum : A novel challenge model - Jiwan K. Chettri; Azmi Al‐Jubury; Inger Dalsgaard; Peter M. H. Heegaard; Kurt Buchmann (Journal of Fish Diseases, 2018)